Dwór Roliczów Parzęczewskich w Parzęczewie, gmina loco, województwo łódzkie, w świetle badań 1988 roku - Wesołek, Przemysław (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
The results of research on the mound (relics of fortified manor house) in Parzęczew, voi. Łódź, are discussed in this article. Works taken in 1988 should be treated as a part of the studies of lay defensive architecture of Łęczyca region in the late medieval and modern period. Their first stage was finished in 1980 by publishing a book by L. Kajzer. Parzęczew is a village laying 25 km north-west from Łódź. In the Middle Ages and modern period it was a small town (town rights in 1421), private property of the Rola Parzęczewski family and the centre of its estate consisting of few villages. The Rola Parzęczewski was a noble and prominent family in Łęczyca district from the end of 14th to the second half of the 16th century. For four generations (1358-1482) people deriving from this family were holding numerous posts in Łęczyca region, although their rank were never high in official hierarchy. In this period Wojciech Parzęczewski was the most eminent and enterprising representative of the family, the one who brought the Parzęczewskis’ fortune to the flowering. The last well known Parzęczewski was Zygmunt, Inowłódz castellan (1538) and Łęczyca castellan (1545). Due to his effort Parzęczew took a reconfirmation of its town rights in 1539. Research that were carried out in Parzęczew in 1988 concerned relics of Parzęczewskis’ manor house which is the mound in the lowering of the river Onida. The object was mentioned in historical sources one time only, during a partition of the family estate in 1450 ("ad fortalido et ad fossae"). The results of this research (which had only sounding and verifying character) are as followed: the recognition of layer stratification inside the mound, confirmation of two phases building, verification of chronology of the whole site. In the first phase (dated broadly to the 15th century) a manor house located on a small, natural islet was built. Nothing can be told about the form of this house, either its fortifications (investigations did not confirm a presence of the moat mentioned in the historical source). However this foundation might be connected with above-mentioned Wojciech. In the second phase (second half of the 16th to half of the 17th century) a conical, 4 m high, mound had been formed on the same place and then a manor house was built. There is scarce evidence to talk about this construction, as well. The manor house was no longer than 10 m. It was constructed as a frame building. It had no cellar. Although during this time Parzęczew had few owners, we may consider the fortified manor house on the mound with Zygmunt Parzęczewski. The general result of the research in Parzęczew showed that construction of a manor house on the mound did not always correspond with time of the family highest prosperity.